Educação patrimonial e desenvolvimento local : relação sociedade-patrimônio em Santa Leopoldina - Castiglioni, Lorena de Andrade (2014)
The study proposes the discussion of the Heritage Education role in conservation process of historic sites in view of its potention as an instrument of generation and/or strengthening of social participation forms and associated with the sense of individu